Meningkatkan Minat Belajar Anak Menggunakan Metode Ceramah Bersama Mahasiswa Kesejahteraan Sosial FISIP USU - Neni Tresna Juliani Laia; Agus Suriadi (Yayasan Literasi Sains Indonesia, 2022)
The children are the golden generation, they will be the support of the nation for better or better in the future. At this very moment, we often meet many children who have a learning problem because it is none other than the lack of interest factor. Entertainment and social media take much of their time away from studying, when study is essential because learning increases their critical and broader thinking. This is what the author found in the PKL I Yayasan Panti Asuhan Menara Kasih Indonesia, Medan.. The writer meets one child who has trouble studying, the child has no real interest in studying. This prompts the writer to be able to dig and help the client to have the passion to learn by case work methods of analyzing problems and in addressing them using the lecture methods. The authors realized that the lecture method was a practical and efficient method used to increase the client's interest in learning. Author, hoping by his doing this method can help a client get out of the problem the client is facing.